When Taekwondo Referees See Red, but It Is an Electronic System That Gives the Points - Apollaro, Gennaro; Falcó, Coral (Frontiers in Psychology, 2021)
Previous studies in taekwondo have considered the use of the manual scoring system or the electronic system with only the use of the electronic body protector. Therefore, the objective of the study is to analyse the relationship between the color protectors and success in 1,327 taekwondo matches from six World Grand Prix Series of two four-year Olympic periods when electronic body and head protectors are used. In the total sample, the results did not show a relationship between the match outcome and the color of the protectors (p = 0.97, C = 0.001). For individual six editions, the results showed a positive and strong relationship between wearing blue protectors and winning matches and one between wearing red protectors and winning matches (p = 0.001, C = 0.19; p = 0.001; C = 0.19). Regarding the weight categories, 8 and 5 of 48 showed higher percentages of blue and red winners, respectively. Regarding sex, males showed a positive relationship between blue color and winning the match in 6 of 24 weight categories, wearing red and winning the match was shown in 2 of 24 weight categories. Females showed a positive relationship between blue color and winning the match in 2 of 24 weight categories, wearing red and winning the match was shown in 3 of 24 weight categories. When it comes to the influence of being a seeded athlete, the results did show a significant confounding effect on the color of the protectors worn by the winner of the match in 2 of 13 weight categories in which a color effect was observed (p = 0.02, C = 0.28; p = 0.02, C = 0.28). In conclusion, wearing red does not provide a higher chance of winning the match. It seems that seeing red has a stronger effect than wearing red, especially in males. Moreover, being seeded athlete does not explain the result of the match. It seems that with the introduction of the electronic helmet protector, in addition to the electronic body protector, made the scoring system more objective, decreasing the advantage of wearing red in winning matches.